Design and construction of the small wind generator called “AR-SF-500” for the ore milling to a laborator y scale - Romero Baylón, Alfonso (2011)
The small wind generator called “AR-SFWP- 500” has a dynamo that generated a potency of 500 watts, which characterize for having in its internal structure, the called “permanent magnet” for working with small wind generators, such as employing in rural zones, where there is a lack of electric energy. In this sense, the purpose of the paper, treats explaining the process of design and construction of the Small Wind Generator AR-SFWP- 500, whose principle of functioning is based in transform the wind energy in electric energy, in such manner, this kind of energy has been used for moving the ore milling at laboratory scale, which uses an electric motor of a lower potency.